Exhaust gas sensor
By increasing the number of grain junction points in the porous protective layer bone particles, its strength is improved, and the problem of insufficient water resistance in existing exhaust sensors is solved, and the durability of the sensor is enhanced.
Patent Information
- Application Number
- CN202080011201.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2019-01-28
- Filing Date
- 2020-01-10
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2040-01-10
AI Technical Summary
The water splash resistance of the porous protective layer in the existing exhaust gas sensors has not been effectively improved in terms of internal observation, which has led to susceptibility to damage in high temperature environments and affects the durability of the sensor.
By increasing the number of more than 3 grain junctions in the bone particles of the porous protective layer, the number in each unit area is within the range of 1 to 10,000 pieces/μm2, thereby improving the strength of the bone particles and enhancing the The water resistance of the porous protective layer.
It effectively improves the water splash resistance of the porous protective layer, reduces the risk of damage in high temperature environments, and extends the service life of the sensor.
Smart Images

Figure CN113366307B_ABST
Abstract
Description
[0001] Cross-reference to related applications
[0002] This application is based on Japanese Patent Application No. 2019-012059 filed on January 28, 2019, and the contents described therein are cited herein. Technical Field
[0003] The present invention relates to an exhaust gas sensor for detecting exhaust gas from an internal combustion engine as a detection target gas. Background Art
[0004] In an exhaust gas sensor for gas detection using the exhaust gas of an internal combustion engine as a detection target gas, a sensor element is used in which a detection electrode and a reference electrode are provided on a solid electrolyte body. A porous protective layer is provided on the surface of the sensor element to protect the sensor element from splashing water. The porous protective layer is formed of ceramic particles such as metal oxides.
[0005] For example, the sensor element of the gas sensor in Patent Document 1 includes: a solid electrolyte body in a cylindrical shape with a bottom, a measuring electrode provided on the outer peripheral surface of the solid electrolyte body, a reference electrode provided on the inner peripheral surface of the solid electrolyte body, and a porous protective layer covering the measuring electrode and allowing the detection target gas to pass. In Patent Document 1, the film thickness and porosity of the porous protective layer are carefully designed to ensure the splash resistance of the sensor element.
[0006] Prior art literature
[0007] Patent Literature
[0008] Patent Document 1: Japanese Patent Application Publication No. 2010-151575 Summary of the invention
[0009] In the conventional gas sensor of Patent Document 1, efforts have been made to observe the porous protective layer superficially and improve the overall properties and characteristics of the porous protective layer. On the other hand, no efforts have been made to observe the porous protective layer internally and improve the splash water resistance required of the porous protective layer.
[0010] Specifically, the porous protective layer is composed of a plurality of aggregate particles of ceramics, etc. The inventors of the present application focused on the state of a plurality of crystal grains constituting the aggregate particles and found that the porous protective layer has improved splash water resistance by making the aggregate particles less susceptible to destruction from a microscopic perspective.
[0011] The present invention is made in order to provide an exhaust gas sensor capable of improving the splash water resistance of a porous protective layer.
[0012] One aspect of the present invention relates to an exhaust gas sensor having a sensor element for performing gas detection using exhaust gas of an internal combustion engine as a detection target gas;
[0013] The sensor element comprises: a solid electrolyte body, a detection electrode provided on the solid electrolyte body and exposed to the detection target gas, and a reference electrode provided on the solid electrolyte body;
[0014] A porous protective layer is provided on at least one of a surface of the detection electrode and a path for guiding the detection target gas to the surface of the detection electrode;
[0015] The porous protective layer is directly composed of a plurality of aggregate particles, or is composed of a plurality of aggregate particles bonded via an inorganic binder;
[0016] When observing a cross section of a plurality of crystal grains constituting the aggregate particles, the number of crystal boundary points where three or more crystal grains intersect is 1 to 10,000 / μm per unit area. 2 within the range.
[0017] In the above-mentioned exhaust gas sensor of one embodiment, the porous protective layer provided on the sensor element is observed from a microscopic perspective, and efforts are made to improve the strength of the skeleton particles constituting the porous protective layer. Specifically, the state of the multiple crystal grains constituting the skeleton particles is focused on, and the number of crystal boundary points where three or more crystal grains in the skeleton particles intersect is made 1 to 10,000 / μm per unit area. 2 within the range.
[0018] Regarding the grain boundary point where more than three grains intersect, when observing the grain boundary where the grains are bonded in the cross section of the porous protective layer, it is observed as a point where more than three grains intersect. It is believed that when the energy of stress such as thermal shock is applied to the porous protective layer, the energy of the stress is transmitted along the grain boundary among the multiple grains constituting the aggregate particles. It is also believed that the energy of the stress is dispersed and transmitted to multiple grain boundaries when passing through the grain boundary point along the grain boundary, thereby attenuating.
[0019] At this time, by making the number of grain boundaries per unit area 1 to 10,000 / μm 2 The number of grain boundaries is appropriate within the range of , and the energy of stress such as thermal shock applied to the aggregate particles can be effectively dispersed. Thus, the strength of the aggregate particles constituting the porous protective layer can be improved, and as a result, the splash resistance of the porous protective layer can be improved.
[0020] Therefore, according to the exhaust gas sensor of one aspect described above, it is possible to improve the splash water resistance of the porous protective layer.
[0021] In addition, the reference numerals in parentheses of the components shown in one embodiment of the present invention indicate the correspondence relationship with the reference numerals in the drawings in the embodiment, but the components are not limited to the contents of the embodiment. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] The objects, features, advantages and the like of the present invention will become more apparent from the following detailed description with reference to the accompanying drawings. The accompanying drawings of the present invention are as follows.
[0023] Figure 1 This is a cross-sectional view showing the exhaust gas sensor in the first embodiment.
[0024] Figure 2 This is a cross-sectional view showing a part of the sensor element of the exhaust gas sensor in the first embodiment in an enlarged manner.
[0025] Figure 3 This is an explanatory diagram showing aggregate particles constituting the porous protective layer formed by thermal spraying in the first embodiment.
[0026] Figure 4 This is an explanatory diagram showing a partial cross section of aggregate particles in the first embodiment.
[0027] Figure 5 This is a cross-sectional view showing another sensor element in the first embodiment.
[0028] Figure 6 This is a graph showing the relationship between the temperature and the standard reaction Gibbs energy of various oxides in the first embodiment.
[0029] Figure 7 This is an explanatory diagram showing a measurement region for calculating the average value of the number of grain boundaries in aggregate particles of the porous protective layer in the first embodiment.
[0030] Figure 8 This is a graph showing the relationship between the number of grain boundaries in aggregate particles and the number of crack splashing in the first embodiment.
[0031] Fig. 9 This is an explanatory diagram showing the energy of stress due to thermal shock applied to the crystal grains of aggregate particles in the first embodiment.
[0032] Fig.10 This is a flowchart showing the method for producing aggregate particles by the electric fusion method in the first embodiment.
[0033] Fig.11 This is a flowchart showing the method for producing aggregate particles by the sintering method in the first embodiment.
[0034] Fig.12This is an explanatory diagram showing aggregate particles constituting the porous protective layer formed by the slurry coating method in the first embodiment.
[0035] Fig.13 This is a cross-sectional view showing an exhaust gas sensor in the second embodiment.
[0036] Fig.14 This is a cross-sectional view showing a part of the sensor element of the exhaust gas sensor in the second embodiment in an enlarged manner.
[0037] Fig.15 A portion of the sensor element in Embodiment 2 is enlarged and shown. Fig.14 XV-XV section view of FIG.
[0038] Fig.16 This is an enlarged view of a portion of the other sensor element in the second embodiment. Fig.14 FIG. 1 is a diagram of section XV-XV of FIG.
[0039] Fig.17 This is a diagram showing a portion of another sensor element in Embodiment 2 which is enlarged and displayed. Fig.14 FIG. 1 is a diagram of section XV-XV of FIG. DETAILED DESCRIPTION
[0040] Preferred embodiments of the exhaust gas sensor will be described with reference to the accompanying drawings.
[0041] <Implementation method 1>
[0042] like Figure 1 and Figure 2 As shown, the exhaust gas sensor 1 of this embodiment has a sensor element 2A, and performs gas detection using the exhaust gas of an internal combustion engine as the detection target gas G. The sensor element 2A has a solid electrolyte body 31A, a detection electrode 311 provided on the solid electrolyte body 31A and exposed to the detection target gas G, and a reference electrode 312 provided on the solid electrolyte body 31A. A porous protective layer 37 is provided on the outer side surface 301 of the solid electrolyte body 31A including the surface of the detection electrode 311.
[0043] like Figure 3 As shown in FIG. 3 , the porous protective layer 37 is composed of a plurality of mutually bonded aggregate particles K1. Figure 4 As shown in FIG. 1 , when observing the cross section of a plurality of crystal grains K2 constituting the aggregate particles K1, the number of crystal boundary points X where three or more crystal grains K2 intersect each other is 1 to 10,000 / μm per unit area. 2 within the range.
[0044] The exhaust gas sensor 1 of this embodiment will be described in detail below.
[0045] (Exhaust gas sensor 1)
[0046] like Figure 1 As shown, the exhaust gas sensor 1 of this embodiment is configured for use in an exhaust pipe 7 for discharging exhaust gas from an internal combustion engine (engine) of a car. The exhaust gas sensor 1 is also called a gas sensor. The exhaust gas sensor 1 is used to detect the oxygen concentration in the detection object gas G. The exhaust gas sensor 1 can also be used to determine whether the air-fuel ratio of the internal combustion engine obtained from the composition of the detection object gas G is on the fuel-rich side or on the fuel-lean side relative to the theoretical air-fuel ratio. In addition, the exhaust gas sensor 1 can also be used as a component for quantitatively determining the air-fuel ratio (A / F) of the engine obtained from the composition of the detection object gas G. In addition, the exhaust gas sensor 1 can also be used as a component for detecting NO in the detection object gas G. x A component that detects the concentration of specific gas components such as (nitrogen oxides).
[0047] A catalyst for purifying harmful substances in the exhaust gas is arranged in the exhaust pipe 7, and an exhaust gas sensor 1 can be arranged on the upstream side or downstream side of the catalyst in the flow direction of the exhaust gas in the exhaust pipe 7. In addition, the exhaust gas sensor 1 can also be arranged on the piping on the suction side of the supercharger, which uses the exhaust gas to increase the density of the air sucked by the internal combustion engine. In addition, the exhaust gas sensor 1 can also be arranged on the intake pipe in the exhaust gas recirculation mechanism, which recirculates part of the exhaust gas discharged from the internal combustion engine to the exhaust pipe 7 to the intake pipe of the internal combustion engine.
[0048] (Sensor element 2A)
[0049] like Figure 2 As shown, the solid electrolyte body 31A of this embodiment has a bottomed cylindrical shape, and the sensor element 2A is a cup-shaped element. The solid electrolyte body 31A has oxygen ions (O 2- ) conductivity. The detection electrode 311 is provided on the outer side surface 301 of the solid electrolyte body 31A exposed to the detection object gas G, and the reference electrode 312 is provided on the inner side surface 302 of the solid electrolyte body 31A exposed to the reference gas. The reference gas may be the atmosphere sucked into the exhaust gas sensor 1, etc. The detection electrode 311 may be provided not only on the outer side surface (outer peripheral surface) 301 of the cylindrical portion of the solid electrolyte body 31A, but also on the outer side surface 301 of the bottom of the solid electrolyte body 31A. The reference electrode 312 may be provided not only on the inner side surface (inner peripheral surface) 302 of the cylindrical portion of the solid electrolyte body 31A, but also on the inner side surface 302 of the bottom of the solid electrolyte body 31A.
[0050] like Figure 1 and Figure 2As shown, the detection electrode 311 and the reference electrode 312 are opposed to each other via the solid electrolyte body 31A at the tip side L1 of the sensor element 2A in the longitudinal direction L. The detection portion 21 is formed at the tip side L1 of the sensor element 2A in the longitudinal direction L, and the detection portion 21 is formed by the detection electrode 311 and the reference electrode 312, and the part of the solid electrolyte body 31A sandwiched between these electrodes 311 and 312. The base end side L2 of the sensor element 2A in the longitudinal direction L is held in the housing 41 of the exhaust gas sensor 1.
[0051] The solid electrolyte body 31A is formed of a zirconium oxide, and is formed of stabilized zirconium oxide or partially stabilized zirconium oxide in which zirconium oxide is mainly composed (containing 50% by mass or more) and a part of the zirconium oxide is substituted with a rare earth metal element or an alkaline earth metal element. A part of the zirconium oxide constituting the solid electrolyte body 31A may be substituted with yttrium oxide, scandium oxide, or calcium oxide.
[0052] The detection electrode 311 and the reference electrode 312 contain platinum as a noble metal showing catalytic activity to oxygen and zirconium oxide as a common material with the solid electrolyte body 31A. When the paste electrode material is printed (coated) on the solid electrolyte body 31A and both are fired, the common material is used to maintain the bonding strength between the detection electrode 311 and the reference electrode 312 formed by the electrode material and the solid electrolyte body 31A.
[0053] Electrode leads for electrically connecting the detection electrode 311 and the reference electrode 312 to the outside of the exhaust gas sensor 1 are connected to the detection electrode 311 and the reference electrode 312. The electrode leads are led out to a portion on the rear end side L2 in the longitudinal direction L of the sensor element 2A.
[0054] (Porous protective layer 37)
[0055] like Figure 2 As shown in FIG. 1 , the porous protective layer 37 is provided on the outer side surface 301 of the solid electrolyte body 31A including the surface of the detection electrode 311. The porous protective layer 37 is provided at the top end side L1 of the solid electrolyte body 31A in the longitudinal direction L. The porous protective layer 37 may be provided continuously to the outer side surface 301 of the bottom of the solid electrolyte body 31A. Figure 5 As shown, the porous protective layer 37 may be provided at a position corresponding to the position where the detection electrode 311 is provided on the outer side surface 301 of the cylindrical portion of the solid electrolyte body 31A.
[0056] like Figure 2As shown, another porous protective layer 38 may be provided on the surface of the porous protective layer 37. The other porous protective layer 38 uses a number of grain boundaries X per unit area of less than 1 / μm. 2 In addition, another porous protective layer 38 may be provided on the outer side surface 301 of the solid electrolyte body 31A, and the porous protective layer 37 may be provided on the surface of the other porous protective layer 38.
[0057] The porous protective layer 37 may be formed with a thickness of 10 to 1000 μm on the outer side surface 301 of the solid electrolyte body 31A and the surface of the detection electrode 311. When a plurality of porous protective layers 37 are formed, the total thickness of the plurality of porous protective layers 37 may be 10 to 1000 μm. When the response speed of the exhaust gas sensor 1 is to be increased, the thickness of the porous protective layer 37 and other porous protective layers 38 may be minimized.
[0058] The porous protective layer 37 can be provided in various ways. For example, the porous protective layer 37 can be formed on the outer side surface 301 of the solid electrolyte body 31A by a sputtering method, and the porous protective layer 37 can be formed on the surface of the porous protective layer 37 formed by the sputtering method by a slurry coating method. These porous protective layers 37 can all be used with a number of grain boundaries X per unit area of 1 to 10000 / μm 2 In addition, the porous protective layer 37 formed by the spraying method and the porous protective layer 37 formed by the slurry coating method can be formed by stacking a plurality of layers.
[0059] (Heater 340)
[0060] like Figure 2 As shown, a heater 340 is arranged on the inner peripheral side of the solid electrolyte body 31A, and the heater 340 is used to heat the solid electrolyte body 31A. The heater 340 is formed by a ceramic substrate 345 and a heating body sheet 346 that is wound on the ceramic substrate 345 and generates heat by energizing. The heating body sheet 346 is formed with: a meandering heating portion 341 and a lead portion 342 connected to the heating portion 341. In order to make the solid electrolyte body 31A and the pair of electrodes 311 and 312 reach the activation temperature, the sensor element 2A is heated by the heater 340.
[0061] (Other Structures of Exhaust Gas Sensor 1)
[0062] like Figure 1As shown in FIG. 1 , in addition to the sensor element 2A, the exhaust gas sensor 1 further includes: a housing 41 for holding the sensor element 2A, a contact terminal 44 in contact with the sensor element 2A, and an insulator 42 for holding the contact terminal 44. In addition, the exhaust gas sensor 1 includes: a top end side cover 45 mounted on the top end side L1 of the housing 41 and covering the top end side L1 of the sensor element 2A; a base end side cover 46 mounted on the rear end side L2 of the housing 41 and covering the insulator 42, the contact terminal 44, etc.; and a bushing 47 for holding the lead wire 48 connected to the contact terminal 44 on the base end side cover 46, etc.
[0063] The tip side L1 portion of the sensor element 2A and the tip side cover 45 are arranged in the exhaust pipe 7 of the internal combustion engine. The tip side cover 45 is formed with a gas passage hole 451 for passing the exhaust gas as the detection target gas G. The tip side cover 45 may be a double-layer structure or a single-layer structure. The exhaust gas as the detection target gas G flowing into the tip side cover 45 from the gas passage hole 451 of the tip side cover 45 passes through the porous protective layer 37 of the sensor element 2A and is guided to the detection electrode 311 on the outer peripheral side of the solid electrolyte body 31A.
[0064] The base end side cover 46 is arranged outside the exhaust pipe 7 of the internal combustion engine. A reference gas introduction hole 461 is formed in the base end side cover 46, and the reference gas introduction hole 461 is used to introduce the atmosphere A into the base end side cover 46. A filter 462 that does not allow liquid to pass but allows gas to pass is arranged in the reference gas introduction hole 461. The atmosphere A introduced into the base end side cover 46 from the reference gas introduction hole 461 passes through the gap in the base end side cover 46 and is guided to the reference electrode 312 on the inner peripheral side of the solid electrolyte body 31A.
[0065] A plurality of contact terminals 44 are arranged on the insulator 42 so as to be connected to the electrode lead portions of the detection electrode 311 and the reference electrode 312 and the lead portion 342 of the heating element sheet 346 of the heater 340. In addition, lead wires 48 are connected to the contact terminals 44 respectively.
[0066] like Figure 1 As shown, the lead 48 in the exhaust gas sensor 1 is electrically connected to the sensor control device 6, which is used to control the gas detection in the exhaust gas sensor 1. The sensor control device 6 cooperates with the engine control device for controlling the combustion operation in the engine to electrically control the exhaust gas sensor 1. The sensor control device 6 is formed with a measurement circuit for measuring the electromotive force generated between the detection electrode 311 and the reference electrode 312.
[0067] In addition, the sensor control device 6 may also be constructed in the engine control device. In addition, in the sensor control device 6, corresponding to the structure of the exhaust gas sensor 1, a measuring circuit for measuring the current flowing between the detection electrode 311 and the reference electrode 312, an applying circuit for applying a voltage between the detection electrode 311 and the reference electrode 312, etc. may be formed.
[0068] (Aggregate particles K1)
[0069] like Figure 3 As shown, the aggregate particles K1 constituting the porous protective layer 37 are exposed to exhaust gas at about 1000°C and are composed of metal oxides with a high melting point. Carbon (C) constituting the fuel component discharged from the internal combustion engine is present in the exhaust gas. When the metal oxide constituting the aggregate particles K1 is easier to reduce than carbon, there is a possibility that the metal oxide constituting the aggregate particles K1 is reduced before the carbon oxide is reduced, causing the aggregate particles K1 to be metallized. In this case, the aggregate particles K1 are easily broken.
[0070] Figure 6 The relationship between the temperature and the standard reaction Gibbs energy of various oxides is shown in . The range of 300-1300°C is set as the operating temperature range of the exhaust sensor 1, and the standard reaction Gibbs energy within this operating temperature range is compared. The standard reaction Gibbs energy represents the energy used to generate and maintain the oxide. The lower the standard reaction Gibbs energy (the larger it is on the negative side), the less likely the oxide is to be reduced. The standard reaction Gibbs energy of oxides of copper (Cu), iron (Fe), etc. is higher (the smaller it is on the negative side) than the standard reaction Gibbs energy of oxides of carbon (C). Therefore, it can be said that oxides of copper, iron, etc. have the property of being easily reduced in the operating environment of the exhaust sensor 1.
[0071] The aggregate particles K1 constituting the porous protective layer 37 are preferably composed of a metal oxide having a standard reaction Gibbs energy lower than that of carbon oxide (larger on the negative side). As a result, the metal oxide is not easily reduced and is easy to maintain the state of the metal oxide (the metal oxide is easy to exist stably) in the use environment of the exhaust gas sensor 1. Therefore, the strength of the aggregate particles K1 constituting the porous protective layer 37 can be maintained at a high level.
[0072] The standard reaction Gibbs energy of oxides of aluminum (Al), magnesium (Mg), etc. is lower (larger on the negative side) than the standard reaction Gibbs energy of oxides of carbon (C). Therefore, it can be said that oxides of aluminum, magnesium, etc. are not easily reduced in the use environment of the exhaust gas sensor 1.
[0073] In addition, for the aggregate particles K1, in addition to oxides of aluminum, magnesium, etc., oxides of silicon (Si), titanium (Ti), calcium (Ca), etc. can also be used. The aggregate particles K1 can be composed of spinel (MgAl2O4), aluminum oxide (Al2O3, aluminum oxide), magnesium oxide (MgO, magnesium oxide), silicon dioxide (SiO2, silicon dioxide), titanium dioxide (TiO2, titanium oxide), calcium oxide (CaO, calcium oxide), etc.
[0074] (Grain boundary point X)
[0075] like Figure 4 As shown, when a cross section of the aggregate particles K1 in the porous protective layer 37 is observed by a microscope or the like, the grain boundary points X can be observed. In the cross section of the aggregate particles K1, a state in which a plurality of grains K2 are joined to each other is observed. In addition, the grains K2 are joined to each other via the grain boundaries R, and the points where the grain boundaries R of more than three grains K2 intersect are observed as grain boundary points X. As the grain boundary points X, there are points where the grain boundaries R of three grains K2 intersect, points where the grain boundaries R of four grains K2 intersect, points where the grain boundaries R of more than five grains K2 intersect, and the like.
[0076] It is considered that there are amorphous (non-crystalline) substances that do not have a crystal structure, impurities that are different from the metal oxides that constitute the aggregate particles K1, etc. at the grain boundary points X. Furthermore, due to the presence of amorphous substances, impurities, etc., at the grain boundary points X, the strength is lower than that of the interior of the grains K2.
[0077] In addition, in the cross section of the aggregate particle K1, there is a portion where a hole H (including a cavity, a gap, etc.) is adjacent to the grain K2. In the portion adjacent to the hole H, the point where the grain boundaries R of more than two grains K2 intersect is not included in the grain boundary point X. In the portion adjacent to the hole H, there is no amorphous, impurity, etc. in the point where the grain boundaries R intersect. Therefore, when stress such as thermal shock is applied to the aggregate particle K1, at the portion adjacent to the hole H, the point where the grain boundaries R intersect does not become a point of energy for dispersing stress. Therefore, in the portion adjacent to the hole H, the point where the grain boundaries R intersect is not included in the number of grain boundary points X.
[0078] (Method for measuring the number of grain boundary points X)
[0079] The number of grain boundaries X in the bone particles K1 can be measured by observing the cross section of the bone particles K1 when cut using an SEM (scanning electron microscope). The bone particles K1 are particles obtained by melting a metal oxide raw material that is a raw material before forming the porous protective layer 37 and forming it into a predetermined particle size. In addition, the porous protective layer 37 is integrally formed with respect to the sensor element 2A as a whole. Therefore, with respect to the formation state of the crystal grains K2 in the bone particles K1, it is considered that the formation state of the crystal grains K2 in the bone particles K1 arranged in any part of the porous protective layer 37 is in the same state.
[0080] The number of grain boundaries X in the aggregate particles K1 of the porous protective layer 37 can be set as an average value of the number of grain boundaries X of the aggregate particles K1 present at a plurality of locations in the porous protective layer 37. The measurement area for measuring the number of grain boundaries X can be, for example, an area of 4 μm in the length direction L and 5 μm in the direction perpendicular to the length direction L on the surface of the porous protective layer 37. The number of grain boundaries X in the measurement area can be measured, and the number of grain boundaries X per 1 μm as a unit area can be calculated from the number. 2 The number of grain boundary points X.
[0081] like Figure 7 As shown in FIG. 1 , the measurement area for calculating the average value of the number of grain boundary points X can be determined by various patterns. For example, on the surface of the porous protective layer 37, a measurement area of 4 μm×5 μm at the highest temperature is specifically defined as the highest temperature measurement area Y1, and an area of 4 μm×5 μm at a position 200 μm away from the top end and the base end of the length direction L is specifically defined as the adjacent measurement area Y2. In addition, for the highest temperature measurement area Y1 and the two adjacent measurement areas Y2, the average value of each 1 μm can be calculated. 2 The number of grain boundary points X can be calculated, and the maximum temperature measurement area Y1 and the two adjacent measurement areas Y2 can be calculated for each 1μm 2 The average value of the number of grain boundary points X.
[0082] In addition, the measurement area for calculating the average value of the number of grain boundary points X may be determined by taking into account the difference in the number of grain boundary points X in the thickness direction of the porous protective layer 37. For example, regarding the measurement area of 4 μm×5 μm on the outermost surface in the thickness direction of the porous protective layer 37, the measurement area of 4 μm×5 μm on the innermost surface in the thickness direction of the porous protective layer 37, and the measurement area of 4 μm×5 μm in the middle position in the thickness direction of the porous protective layer 37, the average value of the number of grain boundary points X per 1 μm can be calculated. 2The number of grain boundaries X can be calculated for each 1 μm in the three measurement areas. 2 The average value of the number of grain boundary points X.
[0083] In addition, the maximum temperature measurement area Y1 and two adjacent measurement areas Y2 on the outermost surface of the porous protective layer 37, the measurement area where the maximum temperature measurement area Y1 and two adjacent measurement areas Y2 overlap in the thickness direction on the innermost surface of the porous protective layer 37, and the measurement area where the maximum temperature measurement area Y1 and two adjacent measurement areas Y2 overlap in the thickness direction at the middle position of the porous protective layer 37 can be calculated for each 1 μm of these nine measurement areas. 2 The average value of the number of grain boundary points X.
[0084] When voids H exist in the measurement region for calculating the average value of the number of grain boundary points X, the area obtained by subtracting the area of voids H from the area of the measurement region is used as the area for measuring the number of grain boundary points X.
[0085] (Number of grain boundaries X)
[0086] like Figure 4 As shown in FIG. 1 , the number of grain boundaries X where three or more grains K2 in the aggregate particle K1 intersect is related to the size of the grains K2 in the aggregate particle K1. There is a tendency that the smaller the size of the grains K2 in the aggregate particle K1, the more the number of grain boundaries X increases. The number of grains K2 in the aggregate particle K1 is preferably 1 to 10,000 / μm. 2 within the range.
[0087] The appropriate number of grain boundary points X where three or more grains K2 intersect per unit area is determined based on the result of investigating the water splashing strength (number of times of cracking water splashing) of the porous protective layer 37. Regarding the water splashing strength, in a computer simulation, a 1 μL water droplet is vertically dripped onto the porous protective layer 37 provided in the sensor element 2A, and the number of times water drops are dripped until cracks are generated in the porous protective layer 37 is determined as a standard. The more times water drops are dripped, the higher the water splashing strength. The temperature of the sensor element 2A when investigating the water splashing strength is set to 500°C, and the thickness of the porous protective layer 37 is set to 100 μm. The position where the 1 μL water droplet is vertically dripped onto the porous protective layer 37 is set as the highest temperature measurement area Y1 on the surface of the porous protective layer 37.
[0088] exist Figure 8 , represents the number of grain boundaries X in the aggregate particles K1 (number / μm 2) and the number of crack splashing (times). The number of grain boundary points X on the horizontal axis and the number of crack splashing on the vertical axis are represented by a logarithmic scale. The results of splashing strength are shown for the case where the porous protective layer 37 is formed by the spraying method and the case where the porous protective layer 37 is formed by the immersion method (slurry coating method). Overall, the porous protective layer 37 formed by the spraying method has a higher splashing strength than the porous protective layer 37 formed by the immersion method.
[0089] It can be seen that the number of grain boundary points X is 1 / μm 2 When using either the spraying method or the dipping method, the water splashing strength is more than 1000 times, and sufficient water splashing strength is obtained. On the other hand, it is known that the number of grain boundary points X is less than 1 / μm. 2 When using either the spraying method or the dipping method, the water splashing strength is about 10 times, and sufficient water splashing strength cannot be obtained.
[0090] In addition, it can be seen that the number of grain boundary points X is 10 to 10,000 / μm. 2 When using either the spraying method or the dipping method, the water splashing intensity is about 100,000 times, and the water splashing intensity is the highest. From this result, it can be seen that the number of grain boundaries X in the aggregate particles K1 is preferably 1 to 10,000 / μm. 2 In the range of 10 to 10000 / μm, more preferably 10 to 10000 / μm 2 within the range.
[0091] In addition, it can be seen that the number of grain boundary points X exceeds 10,000 / μm. 2 It is considered that this is because in this case, the crystal grains K2 in the aggregate particles K1 become too small, the influence of the strain between the aggregate particles K1 increases, and the residual stress in the aggregate particles K1 increases, resulting in a decrease in the strength of the aggregate particles K1.
[0092] (Mechanism of stress absorption in aggregate particles K1)
[0093] like Figure 1As shown, when the exhaust gas sensor 1 is arranged in the exhaust pipe 7 for use, the exhaust gas flowing through the exhaust pipe 7 flows into the top end side cover 45 through the gas passing hole 451 of the top end side cover 45. In addition, the exhaust gas contacts the porous protective layer 37 provided in the sensor element 2A, and the poisonous substances, water droplets, etc. contained in the exhaust gas are captured by the porous protective layer 37. The so-called "poisonous substance" refers to a substance that may poison (degrade) the detection electrode 311 after being attached to the detection electrode 311. As the poisonous substance, there are Si (silicon), S (sulfur), Pb (lead), glass components, soot, etc., which are generated in the internal combustion engine and contained in the exhaust gas, and carbon particles generated by incomplete combustion of organic matter. As the water droplets, there are water that is condensed when the exhaust gas in the exhaust pipe 7 is cooled and is scattered together with the exhaust gas.
[0094] like Fig. 9 As shown, when water droplets or the like contact the porous protective layer 37, stress due to thermal shock is applied to the aggregate particles K1 constituting the porous protective layer 37, which are heated to a high temperature of about 500 to 700°C. At this time, it is considered that the energy of the stress is transmitted along the grain boundaries R among the plurality of crystal grains K2 constituting the aggregate particles K1. Furthermore, the energy transmitted along the grain boundaries R among two adjacent crystal grains K2 passes through the grain boundary point X, which is the intersection point between the two crystal grains K2 and other crystal grains K2.
[0095] At this time, the energy is dispersed at the grain boundary point X and transferred to multiple grain boundaries R. Fig. 9 , the energy S1 transmitted along the grain boundary R is dispersed into a plurality of energies S2 at the grain boundary points X, and then transmitted along a plurality of grain boundaries R. Therefore, the energy is attenuated when passing through the grain boundary points X, and it is considered that the greater the number of grain boundary points X per unit area in the aggregate particles K1, the greater the amount of energy attenuation.
[0096] (Method for producing aggregate particles K1)
[0097] The aggregate particles K1 used to form the porous protective layer 37 of this embodiment are composed of spinel (MgAl2O4) which is an oxide of aluminum and magnesium as a metal oxide. The aggregate particles K1 can be manufactured by an electric melting method or a sintering method. The method of manufacturing the aggregate particles K1 by the electric melting method is as follows: Fig.10 As shown in the flowchart of FIG. 1 , the method for manufacturing the aggregate particles K1 by sintering is as follows: Fig.11 The flowchart is shown in FIG.
[0098] (Electrofusion method)
[0099] When the aggregate particles K1 are produced by the electric melting method, aluminum and magnesium as materials for the aggregate particles are heated at 2500° C. for 0.5 hours in an electric furnace. Fig.10At this time, 0.01 to 5% by mass of a particle growth inhibitor such as ZnO (zinc oxide) may be added relative to 100% by mass of the total amount of the aggregate particle material. Fig.10 In step S02 of the above process, a particle growth inhibitor is mixed into the dissolved aluminum and magnesium. By adding the particle growth inhibitor, the size of the grains K2 in the manufactured aggregate particles K1 and the number of grain boundaries X per unit area can be adjusted.
[0100] The more the amount of the particle growth inhibitor added, the smaller the grains K2 in the aggregate particles K1 become, and the more the number of grain boundaries X per unit area in the aggregate particles K1 becomes. When the amount of the particle growth inhibitor added is less than 0.01 mass %, the particle growth inhibitory effect is insufficient, and there is a possibility that the number of grain boundaries X per unit area in the aggregate particles K1 becomes less than the necessary number. On the other hand, when the amount of the particle growth inhibitor added exceeds 5 mass %, the particle growth inhibitory effect becomes excessive, and there is a possibility that the number of grain boundaries X per unit area in the aggregate particles K1 becomes more than the necessary number.
[0101] In order to make the number of grain boundaries X per unit area 1 to 10,000 / μm 2 , preferably, 0.01 to 5 mass % of a particle growth inhibitor is contained relative to 100 mass % of the metal oxide in the aggregate particles K1. In the aggregate particles K1, the particle growth inhibitor may exist separately from the metal oxide, or may exist in a state of being combined or mixed with the metal oxide. As the particle growth inhibitor, substances other than ZnO may also be used.
[0102] The aggregate particle material is melted and after a predetermined time has passed, the aggregate particle material is cooled and solidified to form an intermediate of the aggregate particle K1 ( Fig.10 At this time, by appropriately adjusting the cooling rate of the aggregate particle material, the number of grain boundaries X per unit area in the aggregate particle K1 can be adjusted. Specifically, the cooling rate of the melted aggregate particle material can be within the range of 10°C / min to 1000°C / sec.
[0103] As a method for cooling the aggregate particle material, a method such as leaving it to stand after heating, blowing air, or water cooling can be adopted according to the cooling rate. When the cooling rate is to be accelerated, blowing air or water cooling can be adopted.
[0104] When the cooling rate is less than 10°C / min, the surface energy of the grain boundary components of the grains K2 in the aggregate particles K1 decreases, and the grains K2 agglomerate, thereby increasing the size of the grains K2. Therefore, there is a possibility that the number of grain boundary points X per unit area in the aggregate particles K1 becomes less than the necessary number. On the other hand, when the cooling rate exceeds 1000°C / sec, the grain growth of the grains K2 in the aggregate particles K1 hardly proceeds. Therefore, there is a possibility that the number of grain boundary points X per unit area in the aggregate particles K1 becomes more than the necessary number.
[0105] In order to make the number of grain boundaries X per unit area 1 to 10,000 / μm 2 The cooling rate of the dissolved aggregate particle material is preferably 10°C / min to 1000°C / sec.
[0106] (Sintering method)
[0107] When the aggregate particles K1 are manufactured by the sintering method, alumina and magnesia as the aggregate particles are mixed, kneaded, dried, and then the mixture of alumina and magnesia is heated to 1000-1600°C and sintered. At this time, alumina and magnesia are solid-dissolved to form spinel ( Fig.11 Depending on the degree of air permeability required for the porous protective layer 37, the aluminum oxide and the magnesium oxide may be formed into either a dense body or a porous body.
[0108] In the sintering method, similarly to the case of the electric melting method, a particle growth inhibitor such as ZnO (zinc oxide) may be added in an amount of 0.01 to 5% by mass relative to 100% by mass of the total amount of alumina and magnesia as the aggregate particle materials. Fig.11 In this case, the effects and the like are the same as those of the case of the electric melting method. In the sintering method, the mixture of aluminum oxide and magnesium oxide is cooled to form an intermediate of the aggregate particles K1, as in the case of the electric melting method. Fig.11 Step S03 in ).
[0109] In addition, in the sintering method, the heating rate (temperature increase rate) for heating the mixture of aluminum oxide and magnesium oxide when sintering, and the cooling rate (temperature drop rate) for cooling the heated mixture of aluminum oxide and magnesium oxide can be 10°C / min to 1000°C / sec. When the heating rate and cooling rate are less than 10°C / min, and when the heating rate and cooling rate exceed 1000°C / sec, the problems are the same as those in the case of the electric melting method.
[0110] (Crushing of intermediate of aggregate particles K1)
[0111] The particle size of the intermediate of the manufactured aggregate particle K1 is larger than the particle size of the aggregate particle K1. Furthermore, the intermediate of the aggregate particle K1 is crushed to obtain aggregate particles K1 ( Fig.10 and Fig.11 The “maximum particle size” represents the maximum diameter in the cross section of the aggregate particle K1.
[0112] (Other manufacturing methods)
[0113] The aggregate particles K1 can also be produced by a spray drying method (spray drying method) or the like in which a liquid or a mixture of a liquid and a solid is sprayed into a gas and rapidly dried to produce a dry powder.
[0114] When the metal oxide constituting the aggregate particle material is alumina, silica, titania, calcia, etc., the aggregate particles K1 can be produced by the above-mentioned electrofusion method or sintering method. The produced aggregate particles K1 are used to form the porous protective layer 37 by spraying, slurry coating, etc.
[0115] (Spraying Method for Forming Porous Protective Layer 37)
[0116] like Figure 3 As shown, the skeleton particles K1 constituting the porous protective layer 37 of this embodiment are not bonded to each other by the inorganic binder B. The porous protective layer 37 can be formed by attaching the skeleton particles K1 to the solid electrolyte body 31A by a spraying method. When the porous protective layer 37 is formed by a spraying method, the skeleton particles K1 in a state of slight surface melting can be sprayed and adhered to the outer side surface 301 of the sintered solid electrolyte body 31A at a high speed and high energy by plasma spraying or the like. In this case, the porous protective layer 37 that is not bonded by the inorganic binder B is formed.
[0117] In the aggregate particles K1 constituting the porous protective layer 37 formed by thermal spraying, the strength of the joints between the aggregate particles K1 is equal to the strength of the interior of the aggregate particles K1. In addition, in the porous protective layer 37 formed by thermal spraying, the grain boundaries R between the crystal grains K2 constituting the aggregate particles K1 are portions with low strength against stress such as thermal shock. When stress such as thermal shock is applied to the porous protective layer 37 formed by thermal spraying, cracks are likely to occur at the grain boundaries R between the aggregate particles K1.
[0118] In the spraying method, the aggregate particles K1 may be sprayed onto the solid electrolyte body 31A by flame spraying, cold spraying, or the like, in addition to spraying the aggregate particles K1 onto the solid electrolyte body 31A by plasma spraying.
[0119] (Slurry Coating Method for Forming Porous Protective Layer 37)
[0120] like Fig.12 As shown, the aggregate particles K1 constituting the porous protective layer 37 may be bonded to each other via an inorganic binder B. The inorganic binder B is mainly used when the porous protective layer 37 is formed by a slurry coating method. When the porous protective layer 37 is formed by a slurry coating method, a slurry formed by mixing the aggregate particles K1 and the inorganic binder B is attached to the outer side surface 301 of the solid electrolyte body 31A by using a method such as dipping (impregnation) or spraying (spraying). Thereafter, the slurry attached to the solid electrolyte body 31A is sintered so that the slurry adheres to the outer side surface 301 of the solid electrolyte body 31A, thereby forming the porous protective layer 37.
[0121] When the slurry is sintered, it is necessary to prevent the characteristics of the sensor element 2A from changing due to heat. Therefore, it is preferable to sinter the slurry at a relatively low temperature of 500 to 1000°C. In addition, for the inorganic binder B, a material that can be sintered at a relatively low temperature is often selected. Therefore, when stress such as thermal shock is applied to the porous protective layer 37 formed by the slurry coating method, a situation in which cracks are easily generated in the inorganic binder B rather than in the aggregate particles K1 is formed.
[0122] However, various technologies have been developed to improve the strength of the inorganic binder B. When the strength of the inorganic binder B is high, it is conceivable that cracks may occur in the aggregate particles K1. Regarding technologies for improving the strength of the inorganic binder B, for example, there is a technology disclosed in Japanese Patent Application Laid-Open No. 2014-178179. When the bonding strength between the aggregate particles K1 obtained by using the inorganic binder B is improved, the possibility of cracks occurring in the crystal grains K2 constituting the aggregate particles K1 increases.
[0123] In addition to the spraying method and the slurry coating method, the porous protective layer 37 may be formed by CVD (chemical vapor deposition), aerosol deposition, etc. However, from the viewpoint of material yield, production cycle time (operation time), etc., the spraying method or the slurry coating method is preferably used.
[0124] (Method of Manufacturing Sensor Element 2A)
[0125] When manufacturing the sensor element 2A, a solid electrolyte body 31A having a bottomed cylindrical shape is prepared, and a plating process is performed to form a reference electrode 312 on the inner side surface 302 of the solid electrolyte body 31A, and a detection electrode 311 is formed on the outer side surface 301 of the solid electrolyte body 31A. Then, the solid electrolyte body 31A having the detection electrode 311 and the reference electrode 312 formed thereon is fired to form the sensor element 2A. Next, the aggregate particles K1 are sprayed on the outer side surface 301 including the detection electrode 311 in the formed sensor element 2A by a spraying method to form a porous protective layer 37.
[0126] In this case, the aggregate particles K1 and the inorganic binder B are attached to the outer side surface 301 including the detection electrode 311 of the sensor element 2A to form the porous protective layer 37, and the porous protective layer 37 is fired.
[0127] (Effect)
[0128] In the exhaust gas sensor 1 of this embodiment, the porous protective layer 37 provided on the sensor element 2A is observed from a microscopic perspective, and efforts are made to improve the strength of the skeleton particles K1 constituting the porous protective layer 37. Specifically, attention is paid to the state of the plurality of crystal grains K2 constituting the skeleton particles K1, and the number of crystal boundary points X where three or more crystal grains K2 in the skeleton particles K1 intersect with each other is set to 1 to 10,000 / μm per unit area. 2 within the range.
[0129] Thus, the number of grain boundaries X contained in the aggregate particles K1 is appropriate, and the energy of stress such as thermal shock applied to the aggregate particles K1 can be effectively dispersed. Therefore, the strength of the aggregate particles K1 constituting the porous protective layer 37 can be improved, and as a result, the splash resistance of the porous protective layer 37 can be improved.
[0130] Therefore, according to the exhaust gas sensor 1 of this embodiment, the splash water resistance of the porous protective layer 37 can be improved.
[0131] In addition, the grain boundary points X are formed three-dimensionally in the aggregate particles K1. Therefore, it is also considered that it is better to obtain the grain boundary points X in the form of the number per unit volume. However, the number of grain boundary points X is observed in the cross section. Therefore, the grain boundary points X are obtained in the form of the number per unit area.
[0132] <Implementation method 2>
[0133] This embodiment shows the exhaust gas sensor 1 in which the solid electrolyte body 31B has a plate shape and the sensor element 2B is a stacked type.
[0134] like Figure 13 to Figure 15As shown, the solid electrolyte body 31B has oxygen ions (O 2- ) conductivity. The detection electrode 311 of this embodiment is provided on the first surface 303 of the solid electrolyte body 31B that is exposed to the detection target gas G; the reference electrode 312 is provided on the second surface 304 of the solid electrolyte body 31B that is located on the opposite side of the first surface 303 and exposed to the atmosphere A. The detection electrode 311 and the reference electrode 312 are opposed to each other via the solid electrolyte body 31B at the top end side L1 in the longitudinal direction L of the sensor element 2B.
[0135] (Gas chamber 35)
[0136] like Fig.14 and Fig.15 As shown, the sensor element 2B of this embodiment has a gas chamber 35 into which the detection target gas G is introduced. The gas chamber 35 is adjacent to the first surface 303 of the solid electrolyte body 31B and is surrounded by the insulator 33 and the solid electrolyte body 31B. The gas chamber 35 is formed at a position in the insulator 33 where the detection electrode 311 is stored. The gas chamber 35 is formed in the form of a space portion enclosed by the insulator 33, the diffusion resistance portion 32, and the solid electrolyte body 31B. The detection target gas G, which is the exhaust gas flowing in the exhaust pipe 7, is introduced into the gas chamber 35 through the diffusion resistance portion 32.
[0137] (Diffusion resistance section 32)
[0138] like Fig.14 As shown, the diffusion resistance portion 32 of this embodiment is formed adjacent to the top end side L1 of the length direction L of the gas chamber 35. The diffusion resistance portion 32 is arranged in the inlet of the insulator 33 which is adjacent to the top end side L1 of the length direction L of the gas chamber 35 and is open. The diffusion resistance portion 32 is formed of a porous metal oxide such as aluminum oxide. The diffusion speed (flow rate) of the detection target gas G introduced into the gas chamber 35 is determined by limiting the speed at which the detection target gas G passes through the pores in the diffusion resistance portion 32.
[0139] like Fig.16 As shown in FIG. 1 , the diffusion resistance portion 32 may be formed adjacent to both sides of the gas chamber 35 in the width direction W. In this case, the diffusion resistance portion 32 is disposed in the inlet of the insulator 33 which is adjacent to both sides of the gas chamber 35 in the width direction W and is open. In addition, the diffusion resistance portion 32 may be formed using a pinhole as a small through hole communicating with the gas chamber 35, in addition to being formed using a porous body of a metal oxide such as alumina. In addition, as Fig.17 As shown, the diffusion resistance portion 32 may be arranged in a state where the gas chamber 35 is filled.
[0140] (Porous protective layer 37)
[0141] like Fig.14 and Fig.15 As shown, the porous protective layer 37 is provided on the surface of the sensor element 2B including the inlet of the gas chamber 35. The inlet of the gas chamber 35 on the surface of the sensor element 2B constitutes a path for guiding the detection target gas G to the surface of the detection electrode 311. In addition, the diffusion resistance portion 32 and the gas chamber 35 constitute a path for guiding the detection target gas G to the surface of the detection electrode 311.
[0142] The porous protective layer 37 of this embodiment is provided on the entire portion of the sensor element 2B at the tip side L1 in the longitudinal direction L. Furthermore, the surface of the diffusion resistance portion 32 is covered with the porous protective layer 37. Fig.17 As shown, the porous protective layer 37 may be provided only around the inlet of the gas chamber 35 in the sensor element 2B (the surface of the diffusion resistance portion 32). On the surface of the porous protective layer 37, the number of grain boundaries X per unit area may be less than 1 / μm. 2 In addition, another porous protective layer 38 may be provided on the surface of the sensor element 2B, and the porous protective layer 37 may be provided on the surface of the other porous protective layer 38.
[0143] The porosity of the porous protective layer 37 is greater than the porosity of the diffusion resistance portion 32 . The flow rate of the detection target gas G that can pass through the porous protective layer 37 is greater than the flow rate of the detection target gas G that can pass through the diffusion resistance portion 32 .
[0144] (Base gas pipeline 36)
[0145] like Fig.14 and Fig.15 As shown, the reference gas conduit 36 surrounded by the insulator 33 and the solid electrolyte body 31B is formed adjacent to the second surface 304 of the solid electrolyte body 31B. The reference gas conduit 36 is formed from the position of the reference electrode 312 in the insulator 33 to the end of the base end side L2 in the length direction L of the sensor element 2B. The reference gas conduit 36 is formed from the end of the base end side L2 to the position opposite to the gas chamber 35 via the solid electrolyte body 31B. The atmosphere A is introduced into the reference gas conduit 36 from the end of the base end side L2.
[0146] (heat generating element 34)
[0147] like Fig.14 and Fig.15As shown, the heating element 34 is embedded in the insulator 33, and has: a heating portion 341 that generates heat by energizing, and a lead portion 342 connected to the heating portion 341. The heating portion 341 is arranged at a position where at least a portion overlaps with the detection electrode 311 and the reference electrode 312 in the stacking direction D of the solid electrolyte body 31B and the insulator 33. The heating portion 341 is formed by a linear conductor portion winding a straight portion and a curved portion. The lead portion 342 is led out to the end portion of the rear end side L2 in the length direction L. The heating element 34 contains a conductive metal material.
[0148] (Insulator 33)
[0149] The insulator 33 is formed using an insulating metal oxide such as aluminum oxide. The insulator 33 is stacked on the solid electrolyte body 31B in order to form the gas chamber 35, the reference gas pipe 36, the diffusion resistance portion 32, and the like.
[0150] (Exhaust gas sensor)
[0151] like Fig.13 As shown, in the exhaust gas sensor 1 of this embodiment, the sensor element 2B is held by the housing 41 via another insulator 43. The other structures are the same as those of the exhaust gas sensor 1 shown in the first embodiment.
[0152] (Method of Manufacturing Sensor Element 2B)
[0153] When manufacturing the sensor element 2B, the sheets constituting the solid electrolyte body 31B, the sheets constituting the insulator 33, etc. are stacked on each other and bonded via an adhesive layer. In addition, on the sheet constituting the solid electrolyte body 31B, a paste material constituting a pair of electrodes 311 and 312 is printed (applied), and on the sheet constituting the insulator 33, a paste material constituting the heating element 34 is printed (applied). And, the intermediate of the sensor element 2B formed by each sheet and each paste material is fired at a prescribed firing temperature to form the sensor element 2B. Next, on the surface of the formed sensor element 2B, the aggregate particles K1 are sprayed by a spraying method to form a porous protective layer 37. In addition, a slurry coating method can also be used instead of the spraying method.
[0154] (Effect)
[0155] In the exhaust gas sensor 1 using the sensor element 2B of the present embodiment, the number of grain boundaries X per unit area may be 1 to 10,000 / μm. 2 The porous protective layer 37 of the aggregate particles K1 within the range of , improves the splash water resistance of the porous protective layer 37.
[0156] The other structures, effects, etc. of the exhaust gas sensor 1 of this embodiment are the same as those of the first embodiment. In this embodiment, components denoted by the same reference numerals as those in the first embodiment are the same as those in the first embodiment.
[0157] The present invention is not limited to each embodiment, and different embodiments can be further constituted without departing from the scope of its gist. In addition, the present invention includes various modifications, modifications within the same scope, etc. Moreover, the combination of various constituent elements envisioned by the present invention, mode, etc. are also included in the technical idea of the present invention.
Claims
1. An exhaust gas sensor having a sensor element and detecting exhaust gas of an internal combustion engine as a detection target gas, The sensor element includes a solid electrolyte body, a detection electrode provided on the solid electrolyte body and exposed to the detection target gas, and a reference electrode provided on the solid electrolyte body. A porous protective layer is provided on at least one of a surface of the detection electrode and a path for guiding the detection target gas to the surface of the detection electrode. The porous protective layer is directly composed of a plurality of aggregate particles, or is composed of a plurality of aggregate particles bonded via an inorganic binder. When observing a cross section of a plurality of crystal grains constituting the aggregate particles, the number of crystal boundary points where three or more crystal grains intersect is 1 to 10,000 / μm per unit area. 2 within the range of The number of the grain boundaries per unit area is an average value of the number of the grain boundaries of the aggregate particles present at a plurality of locations in the porous protective layer.
2. The exhaust gas sensor according to claim 1, wherein: The aggregate particles are formed of metal oxides having a standard reaction Gibbs energy lower than that of carbon oxide.
3. The exhaust gas sensor according to claim 2, wherein: The metal oxide contains at least one of aluminum oxide and magnesium oxide.
4. The exhaust gas sensor according to any one of claims 1 to 3, wherein: The solid electrolyte body has a bottomed cylindrical shape, The detection electrode is disposed on the outer side of the solid electrolyte body exposed to the detection target gas, and the reference electrode is disposed on the inner side of the solid electrolyte body. The porous protective layer is provided on the outer surface of the solid electrolyte body including the surface of the detection electrode.
5. The exhaust gas sensor according to any one of claims 1 to 3, wherein: The solid electrolyte body has a plate shape, The sensor element has a gas chamber for introducing the detection target gas. The detection electrode is arranged in the gas chamber and is provided on a first surface of the solid electrolyte body exposed to the detection target gas, and the reference electrode is provided on a second surface of the solid electrolyte body opposite to the first surface. The porous protective layer is provided on a surface of the sensor element including an inlet of the gas chamber.
6. The exhaust gas sensor according to any one of claims 1 to 3, wherein: The aggregate particles contain 0.01 to 5% by mass of a particle growth inhibitor relative to 100% by mass of the metal oxide in the aggregate particles.
Citation Information
Patent Citations
Gas sensor element and gas sensor incorporating the same
JP2010151575A
Semiconductor device, ultrasonic sensor and moving body
JP2019012059A
Oxygen concentration detector and its manufacturing method
JP2002333422A
Gas sensor and manufacturing method thereof
JP2014178179A
Oxygen sensor
US20070084725A1